Urban Matters : Current Approaches in Variationist Sociolinguistics. - Ziegler, Arne.; Edler, Stefanie; Oberdorfer, Georg (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2021)
This volume discusses the characteristics and dynamics of urban language use, considering aspects such as contact, variation and change, as well as identity, indexicality, attitudes, and spatial factors including mobility, (counter-)urbanisation and diffusion processes. It presents modern methodological and conceptual ideas as well as new findings.
6. Summary and discussion -- 7. Conclusion -- Acknowledgements -- References -- Diminutives and their variation in spoken interaction in urban areas: The Austrian case -- 1. Introduction -- 2. Linguistic situation -- 3. Diminutive suffixes and research questions -- 4. Methodology -- 4.1 Corpora and analytical procedure -- 4.2 Informants -- 5. Results -- 5.1 Multivariate analyses of individual diminutive suffixes -- 5.2 Diatopic view: Vienna and Graz and their surroundings -- 5.3 Diastratic view: Distribution by gender -- 5.4 Diastratic view: Distribution by age -- 6. Conclusions -- Funding -- References -- Areal microvariation in German-speaking urban areas (Ruhr Area, Berlin, and Vienna) -- 1. Introduction -- 2. Aims of the study -- 3. Data, areas and methods -- 3.1 Atlas zur deutschen Alltagssprache (AdA) -- 3.2 German-speaking urban areas (three different ones) -- 3.3 Methods -- 4. Areal variation -- 4.1 Ruhr Area -- 4.2 Berlin -- 4.3 Vienna -- 5. Discussion: The interplay of space and social factors -- 5.1 Ruhr Area -- 5.2 Berlin -- 5.3 Vienna -- 6. Summary -- References -- Testing models of diffusion of morphosyntactic innovations in Twitter data -- 1. Introduction -- 2. Methodology and corpus construction -- 2.1 Corpus structure -- 3. Mapping the distribution of morphosyntactic variants -- 3.1 Dative alternation revisited -- 3.2 Preposition drop -- 4. Approaches to the quantification of diffusion -- 4.1 Measurement -- 4.2 Evaluating real data -- 5. Conclusions -- Funding -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books